2014
DOI: 10.1371/journal.pone.0093008
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Malarial Cysteine Proteases and Falstatin: The BC Loop as a Hot-Spot Target

Abstract: Cysteine proteases play a crucial role in the development of the human malaria parasites Plasmodium falciparum and Plasmodium vivax. Our earlier studies demonstrated that these enzymes are equipped with specific domains for defined functions and further suggested the mechanism of activation of cysteine proteases. The activities of these proteases are regulated by a new class of endogenous inhibitors of cysteine proteases (ICPs). Structural studies of the ICPs of Trypanosoma cruzi (chagasin) and Plasmodium berg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A, B, C, and D, and hence desired drug interaction could be obtained by any chain/monomer. However, for performing docking studies chain B was selected because only its sequence was complete and was devoid of any mutations …”
Section: Methodsmentioning
confidence: 99%
“…A, B, C, and D, and hence desired drug interaction could be obtained by any chain/monomer. However, for performing docking studies chain B was selected because only its sequence was complete and was devoid of any mutations …”
Section: Methodsmentioning
confidence: 99%
“…Substantial effort has been made to develop rational strategies in designing PPI inhibitors for target proteins that have no well-defined binding site (so-called "hot-spot") and, thus, have previously been considered undruggable (Figure 4). [44,45].…”
Section: Ppi Inhibition: Peptidomimetics and Designmentioning
confidence: 99%
“…More importantly, three loop regions termed BC-, DE-, and FG loops Protein-Protein Interactions in Malaria: Emerging Arena for Future Chemotherapeutics DOI: http://dx.doi.org /10.5772/intechopen.89217 were shown to be involved in active site inhibition (Figure 5A,B) [44]. However, further studies with the P. falciparum ICP, falstatin, indicated that unlike other ICPs, just the BC loop was sufficient for falcipain inhibition and that Asn289 of falstatin formed stabilizing hydrogen bonds and hydrophobic interactions ( Figure 5C,D) [45].…”
Section: Ppi Inhibition: Peptidomimetics and Designmentioning
confidence: 99%
“…Later, utilizing site-directed mutagenesis, hemoglobin hydrolysis assays and peptide inhibition studies, Indian investigators demonstrated that only the first loop (BC) specifically inhibits FPs and VPs via hydrogen bonds. This loop was suggested as a drug target for development of an effective potent antimalarial novel CPI [158] .…”
Section: [Iii] Cystatins (Cyss)mentioning
confidence: 99%